Bone harvesting with 3D printed, computer-planned osteotomy guide for the reconstruction of a challenging Seibert Class III defect. (June 2022) - Greco, Alessandro
Abstract : Purpose: Reconstruction of Seibert class III alveolar ridge deficiencies requires bone augmentation before implant placement. Autogenous bone graft is still considered the gold standard for hard tissue regeneration. Ramus buccal shelf offer advantages over external donor sites such as convenient surgical access and decreased morbidity. The risk of damage to anatomical structures is related to the absence of three-dimensional control of the cutting planes. There is further concern regarding the reconstruction of wide defects in the presence of scarce donor sites. A protocolled digital workflow has been introduced to help the surgeon during this phase (Safecut®). Methods: This case report describes the procedure in a partially edentulous, brachycephalic patient with a challenging 3D defect in the upper right maxilla, a short donor site, and muscular encumbrance. The risk for suboptimal freehand harvest was identified by the surgeon, thus opting for a guided approach. The ideal dimension of the bone block was planned through a computer-aided design (CAD) process in close interaction with the laboratory. DICOM data from pre-operative CBCT were matched with cast scan STL file in order to fabricate a 3D printed stent with a tooth reference in order to facilitate the proper installation of the guide. Results: The surgical intervention was conducted in a low-stress environment allowing the surgeon to concentrate on the reconstruction of the defect. Conclusions: This case showed the potential of digital planning and computer-guided bone harvesting to minimize the invasiveness of the procedure.